Case report: identification of novel variant in SLC26A2 gene and preimplantation genetic testing for monogenic disorders in preventing diastrophic dysplasia - Ziravard N. Tonyan; Yulia A. Nasykhova; Maria M. Danilova; Elena S. Shabanova; Olesya N. Bespalova; Igor Y. Kogan; Andrey S. Glotov (Egyptian Journal of Medical Human Genetics)
Abstract Background Diastrophic dysplasia is a rare autosomal recessive disorder characterized by abnormalities in bone and cartilage development, caused by pathogenic variants in the SLC26A2 gene. Case presentation This article presents a clinical case of preimplantation genetic testing for monogenic disorders (PGT-M) conducted for a family with two previous pregnancy losses due to diastrophic dysplasia in the fetus. We report a previously uncharacterized variant c.1358C > T in the SLC26A2 gene associated with diastrophic dysplasia. We detail the approach to performing PGT-M in the absence of material from the proband and close relatives from one partner for analysis. A testing system was developed to analyze pathogenic variants in the SLC26A2 gene, alongside with indirect markers such as short tandem repeats and single nucleotide polymorphisms. This allowed us to identify linkage groups associated with the analyzed pathogenic variants during the in vitro fertilization cycle with PGT-M, enabling the selection of an embryo that did not inherit pathogenic variants from either parent. The transfer of this embryo resulted in a successful pregnancy, resulting in the birth of a healthy child. Conclusion To our knowledge, this is a first report of variant c.1358C > T in the SLC26A2 gene associated with diastrophic dysplasia. The successful application of PGT-M enabled the selection of an embryo free from inherited pathogenic variants from both parents, highlighting the importance of PGT-M in improving reproductive outcomes for affected families.